Analisis Faktor-Faktor yang Mempengaruhi Tingkat Bagi Hasil Simpanan Mudharabah pada Bank Umum Syariah Indonesia Studi Kasus pada Bank Umum Syariah di Indonesia Periode 2011-2015 - Lydia Rahmadhini Arfiani; Ade Sofyan Mulazid (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
This study aims to determine Analysis of Factors Affecting Level Sharing Mudharabah Savings On Islamic Banks partially or simultaneously on Bank Syariah period 2011-2015. The population in this study is the Islamic Banks operating in Indonesia 2011-2015. This study using purposive sampling method with variable FDR, NPF and inflation at the level of the results. After being selected, the target population amounted to 7 banks, among the BCA Syariah, BNI Syariah, BRI Syariah Bukopin Syariah Mandiri Syariah Muamalat, Panin Syariah. The analytical method used is the panel data regression. The model chosen is the Fixed Effects Model, then tested by t test and f with a significance level of 5%. Based on the test f note that in this study the variable financing to deposits ratio and non-performing financing and inflation simultaneously affect the level of revenue sharing sharia banks. Based on t test is known that in partial financing to deposits ratio, non-performing financning which have an influence on the level of revenue sharing sharia banks. Adjust R2 in this study indicate that all independent variables contributing as much as 51% on the dependent variable. The remaining 49% is influenced by other variables that do not exist in this study such as CAR, interest rate, economic growth.